KEBIJAKAN PENANGGULANGAN DEFORESTASI DI KABUPATEN ROKAN HILIR TAHUN 2011-2012 - Yunda Wahyuni; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study is intended to determine the deforestation reduction policy in Rokan Hilir. This study focused on prevention of deforestation in Rokan Hilir. Deforestation in Rokan Hilir is due to land and forest fires, illegal logging and forest clearing also be used as land conversion. With the formulation of research problems that How deforestation reduction policy in Rokan Hilir and the factors that affect deforestation reduction policy in Rokan Hilir. Based on the above, the study aims to identify and analyze deforestation reduction policy in Rokan Hilir. The research method is qualitative descriptive research data collection was done by interview and documentation.From the results of field research shows in forest fire prevention has not run optimally, it can be seen from the response such as the creation of the canal. Not all districts made canal just a few. Later in the prevention of illegal logging, there is still a lack of law enforcement efforts to make the perpetrators of illegal logging with companies and people still continue to deforestation. Later in the prevention of land conversion has not run optimally. This is evident from the lack of decisive action or sanctions against companies that do encroachment of forest areas and in charge functioned into plantations. The factors that affect the implementation of the policy response to deforestation in Rokan Hilir, through the theory of policy implementation, namely: Target and policy standards, performance policies, resources, communication between implementing agencies, Characteristics implementing agencies, economic environment, social and political and Attitudes implementers. In this study, the authors conclude that the Government Rokan Hilir either through the Forest Service has not been serious in handling the destruction of forests (deforestation) that occurred in Rokan Hilir. But the Government should Rokan Hilir especially its policy making in addressing deforestation in Rokan Hilir.Keywords: Policy, Mitigation, Deforestation.